Unraveling the function of CD11B+ myeloid cells in the tumor microenvironment - Clemente, Ana Cláudia Dourado, 1990- (2016)
Tese de mestrado, Oncobiologia, Faculdade de Medicina, Universidade de Lisboa, 2015